Nonfiction Text Teaching Materials in Indonesian Language Learning - I Gusti Lanang Agung Pratama Wiguna; I Nyoman Sudiana; Ermalinda Yosefa Awe; M. Zainal Mustamiin; M. Taufik (Universitas Pendidikan Ganesha, 2025)
The development of nonfiction text teaching materials is an important aspect of improving the quality of Indonesian language learning in elementary schools, particularly in strengthening students’ literacy and critical thinking skills. However, the teaching materials currently used in elementary schools remain limited and are not yet fully contextual or research-based. This study aims to systematically review research findings related to the development of nonfiction text teaching materials and to analyze their implications for Classroom Action Research (CAR). This study employed a Systematic Literature Review (SLR) method, with the research subjects consisting of scientific articles published in national and international journals indexed in Google Scholar, ERIC, DOAJ, and SINTA. Data were collected through a documentation study using inclusion and exclusion criteria to select relevant articles, while data analysis was conducted using qualitative content analysis and thematic synthesis techniques. The results indicate that nonfiction text teaching materials developed in a contextual, student-centered manner and aligned with the curriculum are able to improve reading comprehension, writing skills, and student engagement in the learning process. The integration of SLR findings into Classroom Action Research provides a reflective framework for teachers to improve instructional practices through cycles of planning, action, observation, and reflection. Thus, the development of evidence-based teaching materials becomes an effective strategy for enhancing Indonesian language learning in elementary schools.